Implementation of six sigma approach for increasing quality formal men’s jackets in the garment industry - Sjarifudin, Didin; Kurnia, Hibarkah; Purba, Humiras Hardi; Jaqin, Choesnul (Universitas Serang Raya, 2022)
This study aims to implement the Six Sigma method on formal men's jacket products in the garment industry to increase the level of sigma. The methodology is based on the Define, Measure, Analyze, Improve, and Control (DMAIC) approach. The new approach in this study is the determination of 5W+1H using a Focus Group Discussion (FGD) with five expert judgments. The design of this study has applied the Six Sigma method at the Measure stage. It is a measurement before improvement and after the Control stage as a measurement after improvement. The results of this study have increased the level of sigma from 3.5765 to 3.7839, so there is an increase of 5.48%. Increasing the sigma level contributes to a decrease in defects at the finish line by 44.09% every month. Implementing the Six Sigma method to the DMAIC approach has succeeded in increasing the level of sigma, automatically reducing the percentage of defects and increasing the productivity of formal men's jackets in the garment industry.